Pengaruh Metode Circuit Training Terhadap Daya Tahan Otot Pada Atlet Panjat Tebing Federasi Panjat Tebing Indonesia - Sukarman, Sukarman (CV Insan Kreasi Media, 2024)
Based on observations made by Wall climbing researchers, Central Lombok Indonesian Rock Climbing Federation (FPTI) athletes still have short comings when training, including a lack of arm muscle training. This may be seen during activities where arm mobility is poor, resulting in less than ideal climbing speed. The aim of this research is to determine the effect of circuit training on muscle endurance in Central Lombok Indonesian Rock Climbing Federation (FPTI) athletes in the Lead category. The type of research used is experimental and the design in this research is one group pretest-posttest design, where according to Sugiyono (2008: 83) in this design there is a pretest, before being given treatment. The population in this study were all athletes from the Indonesian Rock Climbing Federation (FPTI) Central Lombok, totaling 5 men and 5 women. In this research the entire population will be used as a sample so this research is called population study research. Based on the data required in this research which is primary data, data collection was carried out by carrying out a test, namely the Side Learning Test, this test instrument aims to measure the level of arm muscle endurance (Widiastuti, 2011:184-185). From the results of statistical data analysis of circuit training exercises, t count > t table (8.104 > 1.833), on the muscle endurance of rock climbing athletes so that the t count value, the simultaneous value between Y and n-1 (10-1 = 9) which is 1.833, it can be concluded that